Rethinking conceptions of body image in group fitness education, culture, and contexts: Recommendations for perspective transformation and innovations in instructional methods - Dobrich, Emily O. R. (Frontiers in Education, 2022)
This article examines the situation of group fitness instructors with particular attention to the implications of the influence of fitness culture on body-related norms which shape instructors’ self-perceived conceptions of body image. Of particular interest is the consideration of how self-perception influences an instructor’s performance, and their ability to educate and motivate their class participants. Evidence will show that the most popular ways that body image is incorporated into and represented within the group fitness setting are limiting and misguided, and there are better methods for instruction that fitness professionals and the industry can follow. Recommendations for practice and suggestions for interventions to encourage adequate body satisfaction in the group fitness instructor’s context will be provided for both individual and collective levels of action. This will include what instructors can do at an individual level to improve their self-perceptions and professional practice and support themselves and their peers; what can be done in gyms and fitness facilities to improve community support for instructors; and what can be done at the fitness industry level to encourage a cultural shift in body-related norms and expectations.